RESEARCH OF WIDEBAND HYDRO ACOUSTIC SYSTEM, CONTAINING TRANSDUCERS OF WAVEGUIDE TYPE - Ivan S. Pesterev; Boris G. Stepanov (Известия высших учебных заведений России: Радиоэлектроника)
The results of experimental research of models of antennas hydroacoustic system (HAS), containing transducers of the waveguide type (TWT), which represent a coaxial set of identical water-filled piezocylinders, electrically excited by the principle of a traveling wave formation in the inner cavity of the TWT, are given. Possibilities of the TWT are analyzed when they are excited in accordance with the solution of the synthesis problem for the investigated HAS. The realization of such excitation is carried out by means of software-controlled multichannel blocks and allows providing a close to uniform amplitude-frequency characteristic of radiation and linear phase-frequency characteristic of radiation in a 3-octave frequency band. The possibility of radiation in this band of ultrashort pulses, tunable in frequency, as well as the formation of signals similar to the signals of cetaceans, is shown. The influence of the number of active piezocylinders of the TWT and the character of its electric excitation on the frequency and impulse response of the investigated HAS is considered. Directional properties of models of antennas HAS, including scanning and pulse operation modes, are considered. A comparative evaluation of the calculated and experimental data, as well as an evaluation of the efficiency of the TWT radiation, is given.